Snow White and the Seven Dwarfs New Perspectives on Production, Reception, Legacy - Pallant, Chris; Holliday, Christopher (Animation: Key Films/Filmmakers, 2021)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com Walt Disney's Snow White and the Seven Dwarfs (David Hand, 1937) occupies a central place within the history of global animation. Based on the German fairy tale by the Brothers Grimm, the film was the first feature-length animated film produced by the Disney Studio and served to announce the animated cartoon as an industrial art form. Yet Disney's landmark version not only set in motion the Golden Age of the Hollywood cartoon, but has continued to stand as an international sensation, prompting multiple revisions and remakes within a variety of national filmmaking contexts. This book explores the enduring qualities that have marked Snow White's influence and legacy, providing a collection of original chapters that reflect upon its pioneering use of technology and contributions to animation's visual style, the film's reception within an American context, and its status as a global cultural phenomenon.